Peningkatan Kompetensi Menggambar Teknik Siswa SMK-SMA dengan AutoCad Di Surabaya-Gresik - Abdullah, M Hasan; Purnamayudhia, Onny; Hindratmo, Astria; Octavia, Chendrasari Wahyu (Fakultas Teknik-Universitas Wijaya Putra, 2023)
The rapid development of science and technology is a challenge as well as an opportunity for the field of education and industry. Mastery of technology is also a must for SMK (Vocational High School) students who are prepared to enter the industrial world upon graduation. One of the basic skills that need to be mastered is drawing techniques. Through community service activities, the Faculty of Engineering, Wijaya Putra University, Surabaya provides basic training in engineering drawing using Autocad software. The training participants were attended by several SMK and SMU students in Surabaya. The training begins with an introduction to Autocad and its use in various professional fields. Pre-test and post-test are given to determine the level of understanding of participants. Participants were also given 2D and 3D drawing tasks. In addition to drawing training, students are also given insights regarding the Faculty of Engineering and the career opportunities that will be obtained. This training received a positive response from students and schools.